PUBLIC’S VIEW ON THE EXTENDED SERVICE HOUR IN SINGKAWANG PUBLIC SERVICE MALL FROM 19.00-21.00 WEST INDONESIA TIME - Lestari, Yeni; Julian, Edwin; Lazuardi, Dwika Restu An Nahl (Registratie, 2024)
Public service mals are made to improve the quality of public services, especially the government makes a policy for night services at the Singkawang City public service mal. Therefore, this study aims to determine the public's perception of night service policies (19.00-21.00) at public service mals in Singkawang City. The type of this research is qualitative with data collection techniques in the form of observations, surveys, and interviews. Sources of data used are primary and secondary data. The data obtained is then analyzed descriptively (qualitatively and quantitatively) based on grouping, simplification, and presentation in the form of a simple diagram of the results of the questionnaire, and the results of the interviews will be analyzed and concluded as well as a comparison between one another. And found the results of a survey of 130 respondents, as many as 68% of respondents answered that public service mals are useful, 37% often go to public service mals, 72% of respondents often go to public service mals during the day, 71% of respondents agree with night service policies, for the time being service and employee performance is very good, 57% of respondents agree with the extension of service hours at night. From the results obtained, it can be concluded that the community is happy with the night service policy at the public service mall because the community has a lot of activities during the day.